Article Review Potensi Senyawa Ginkgolide dan Bilobalide dalam Ekstrak Daun Ginkgo Biloba sebagai Terapi Penyakit Parkinson - Karima, Khaula; Gina Syafinatunnajah; Haditya Novan Kasprata; Irsyadina Hasana Bharata; Jihan Alifa Rahma; Herpan Syafii Harahap (Lombok Medical Journal, 2023)
Parkinson's disease is a neurological disorder that can be a major source of disability throughout the world. Changes in conditions in the body, such as Î±-Syn mutations can increase the risk of developing Parkinson's disease. Î±-Syn mutations will cause the loss of large and selective dopaminergic neurons in the substantia nigra pars compacta (SNpc) thereby triggering the early symptoms of Parkinson's disease. The high risk of side effects in the use of modern pharmacological therapy, indicates that a new breakthrough in the form of herbal-based ethnomedicine therapy for patients with Parkinson's disease is urgently needed. Ginkgo leaf, from the Ginkgo biloba plant, has long been known as a popular herbal supplement in Europe, Asia and America. The content of active compounds in ginkgo leaves was found to have the potential to provide therapeutic effects in patients with Parkinson's disease. This article will discuss the potency, mechanism of action, extraction process, and comparison of the potency of the two compounds with previous therapies. The development of the potential of ginkgo leaves is expected to reduce the increasing number of cases and provide a better quality of life in patients with Parkinson's disease.